Community Law Laboratory (Laboratorium Hukum Masyarakat) as a Participatory Socio-Legal Intervention for Inclusive Tourism Village Development: Evidence from Lerep Village, Indonesia - Muhammad Azil Maskur; Dede Indraswara; Wildan Azkal Fikri; Yustina Dhian Novita; Muhamad Helmi Md Said (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2026)
The development of tourism villages often creates a paradox: economically successful yet exclusive towards vulnerable groups. Lerep Village, as a premier destination, faces an acute normative-empirical gap between legal ideality (Semarang Regency Regional Regulation No. 12/2021) and the reality of infrastructural exclusion for persons with disabilities. This community service research aims to (1) analyze the factors causing this exclusion and (2) evaluate the effectiveness of the Community Law Laboratory (LHM) as a participatory socio-legal intervention to bridge this gap. Employing a socio-legal approach operationalized through the Participatory Rural Appraisal (PRA) methodology, the intervention was conducted over a 12-month period (October 2025 – October 2026). The methodology was executed through a six-step systematic framework: normative assessment, stakeholder mapping, participatory mapping (including transect walks), pair-wise ranking for problem prioritization, action plan formulation, and evaluation. The program engaged approximately 100 participants, alongside 30 village officials and tourism managers. The LHM effectively acted as a "socio-legal incubator". Through these specific PRA techniques, the intervention successfully dismantled the charitable paradigm among the village apparatus, shifting it toward a human rights-based approach. This collective awareness resulted in the participatory formulation of an Inclusive "Design and Build" Action Plan, designed for integration into the Village Budget (APBDes). By transforming abstract legal norms into concrete local policies, the PRA-based LHM model provides a scalable framework for other tourism villages in Indonesia to actively advance the Sustainable Development Goals (SDGs), specifically SDG 10 (Reduced Inequalities), SDG 11 (Sustainable Cities and Communities), and SDG 16 (Peace, Justice, and Strong Institutions).